Ability in Using Chinese Adverb “Tongchang” and “Changchang” of STBA-PIA Second Year Student 2017/2018 Academic Year - Yenny Marlim; Yanti Yanti (Journal of Language, Literature and Teaching, 2020)
The research is aimed at discovering the ability of STBA-PIA Second Year Students 2017/2018 Academic Year in using the Chinese Adverb “Tongchang通常” and “Changchang 常常”. This research uses a descriptive quantitive design method with a total population of 67 students. As the total population is under 100, the whole students are taken as the research sample. Students’ ability in using both Chinese Adverbs “Tongchang通常” and “Changchang 常常” is measured by using the test in which is the research instrument. The validity and reliability of the research instrument are examined by using content validity and internal reliability. Internal reliability is examined by using Kuder Richardson 20 formula. The reliability of the instrument shows the coefficient of 0.618 in which may be interpreted as quite a strong value. After passing the reliability score, the instrument is given a test to students. The result of the test is the ability of STBA-PIA second-year students in using the Chinese Adverb “Tongchang通常” and “Changchang常常” can be categorized as quite competent as 61.18% of students reach the average score of 74.72 for “Tongchang通常”  and 63.18% of students reach the average score of 72.04 for “Changchang 常常”.Keywords: Cognitive Ability, Chinese Adverb, 通常 (tongchang), 常常 (changchang).